PERAN PENGASUH PANTI ASUHAN DALAM MEMENUHI KEBUTUHAN SOSIAL ANAK (Studi Pada Panti Asuhan Al-Ikhlas di Kecamatan Baruga Kota Kendari) - Musdalifah Dirgantari Mustafa; Suharty Roslan; Aryuni Salpiana Jabar (Universitas Halu Oleo, 2023)
This study aims to determine the role of orphanage caregivers in meeting the social needs of children in the Al-Ikhlas orphanage, Baruga District, Kendari City and to determine the condition of the social needs of children in the Al-Ikhlas orphanage, Baruga District, Kendari City. Kendall City. This type of research is qualitative research. Determination of informants in this study used a purposive sampling method so that the informants in this study were head of the orphanage, secretary of the orphanage, administrators of the orphanage and foster children. Data collection techniques used are observation, interviews, documentation. Sources of data used are primary data and secondary data. The data analysis technique uses a qualitative approach with the following steps: data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that caregivers have played a role as educators, parents, mentors, givers of affection, and motivators. The social needs of children in orphanages include physiological needs, safety needs, attention and affection needs, social needs, health needs, and educational needs (formal and non-formal).